(untitled) (CIPEEX, 2022)
BURNOUT SYNDROME IS CHARACTERIZED AS A PSYCHOGENIC PATHOLOGY DUE TO EMOTIONAL EXHAUSTION, THE FEELING OF FRUSTRATION ASSOCIATED WITH LOW PERSONAL FULFILLMENT AND DISBELIEF. IT IS OBSERVED, THEREFORE, THAT THIS DISEASE HAS HAD A HIGH INCIDENCE AMONG THE STUDENTS OF THE HEALTH AREA, NOT ONLY HINDERING THEIR PROGRESS, BUT ALSO IMPEDING THEM IN VARIOUS WAYS TO TAKE ADVANTAGE OF THE COURSE IN ITS COMPLETENESS. IN THIS SENSE, RESEARCH ON THE CAUSES OF THIS PROBLEM BECOMES OF PARAMOUNT IMPORTANCE, SINCE THE IMPACT ON THE QUALITY OF LIFE OF THOSE AFFECTED REFLECTS A NEGATIVE PSYCHOSOCIAL DEVELOPMENT. THEREFORE, THE PURPOSE OF THIS SUMMARY IS TO MAKE A LITERATURE REVIEW ABOUT BURNOUT SYNDROME IN UNIVERSITY STUDENTS NOT ONLY IN THE MEDICAL SCHOOL, BUT IN ALL HEALTH AREAS, CORRELATING SOCIODEMOGRAPHIC AND ECONOMIC DATA WITH STRESSORS, SHOWING ITS AMPLITUDE AND SEVERITY. TO DO SO, WE SEARCHED THE DATABASES ONLINE, SUCH AS SCIELO, PUBMED AND GOOGLE SCHOLAR, SO THAT ONLY THOSE ARTICLES THAT INCLUDED THE OBJECTIVES OF THE RESEARCH AND WHOSE PUBLICATION WAS RECENT AND WELL QUALIFIED WERE SELECTED. IN THE PART OF RESULTS AND DISCUSSIONS, IT IS NOTICED THAT, AMONG THE COMPONENT DIMENSIONS OF THE APPLIED QUESTIONNAIRE (MBI-SS), ALL SELECTED ARTICLES OBTAINED THEIR HIGHEST SCORES IN EMOTIONAL EXHAUSTION AND THE LOWEST IN PROFESSIONAL ACHIEVEMENT, CHARACTERIZING THE SYNDROME IN PEOPLE WITH TRAITS TYPICAL OF IT. THEREFORE, THE NEED FOR FURTHER RESEARCH IN THIS AREA IS APPARENT, PREFERABLY WITH A LARGER SAMPLING AND LONGITUDINAL APPROACH AND ACTIVITIES THAT PREVENT THE DEVELOPMENT OF SB IN YOUNG STUDENTS.